Pemasangan Petunjuk Arah Menuju Lapangan Sports Center Desa Kloposepuluh oleh Mahasiswa KKN Universitas Sunan Giri Surabaya - Laila Torfiah; Jihan Millah Al-firdaus; Cilda Thesisa Ilmawan Dzinnur; Bambang Triono; Moh. Syaiful Anwar; Didit Darmawan; Fahmy Ryadin (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
This research was conducted in Kloposepuluh Village, where the Kloposepuluh Village field lacks directions that make it easier for local residents to find it. In an effort to promote the field and help villagers, this research uses the ABCD (Asset Based Communities Development) method, which is an asset-based community development approach. The focus is on utilizing the existing potential within the community. The village field was not only identified as a sporting venue, but also as a multifunctional area to play and relax with family or friends. The beauty of the field surrounded by plantations and rice fields makes it an ideal place to take pictures. KKN students from Sunan Giri University Surabaya have conducted a study that resulted in the installation of directions to Kloposepuluh Village Sports Center Field, making a positive contribution in introducing the field to the local community and improving its accessibility.